Impact of harm minimization interventions on reducing blood-borne infection transmission and some injecting behaviors among people who inject drugs: an overview and evidence gap mapping - Fernanda S. Tonin; Filipa Alves da Costa; Fernando Fernandez-Llimos (Addiction Science & Clinical Practice, 2024)
Abstract Background This study aimed to synthetize the evidence on the effectiveness of harm minimization interventions on reducing blood-borne infection transmission and injecting behaviors among people who inject drugs (PWID) through a comprehensive overview of systematic reviews and evidence gap mapping. Methods A systematic review was conducted with searches in PubMed and Scopus to identify systematic reviews assessing the impact of interventions aimed at reducing the harms associated with injectable drug use. The overall characteristics of the studies were extracted and their methodological quality was assessed using AMSTAR-2. An evidence gap map was constructed, highlighting the most frequently reported outcomes by intervention (CRD42023387713). Results Thirty-three systematic reviews were included. Of these, 14 (42.2%) assessed the impact of needle/syringe exchange programs (NSEP) and 11 (33.3%) examined opioid agonist therapy (OAT). These interventions are likely to be associated with reductions of HIV/HCV incidence (10–40% risk reduction for NSEP; 50–60% for OAT) and sharing injecting paraphernalia (50% for NSEP, 25–85% for OAT), particularly when combined (moderate evidence). Behavioral/educational interventions were assessed in 12 reviews (36.4%) with most authors in favor/partially in favor of the use of these approaches (moderate evidence). Take-home naloxone programs and supervised-injection facilities were each assessed in two studies (6.1%), which reported inconclusive results (limited/inconsistent evidence). Most authors reported high levels of heterogeneity and risk of bias. Other interventions and outcomes were inadequately reported. Most systematic reviews presented low or critically low quality. Conclusion The evidence is sufficient to support the effectiveness of OAT, NSEP and their combination in reducing blood-borne infection transmission and certain injecting behaviors among PWID. However, evidence of other harm minimizations interventions in different settings and for some outcomes remain insufficient.